2021
DOI: 10.1177/03000605211006610
|View full text |Cite
|
Sign up to set email alerts
|

Roles of preoperative and early postoperative electrodiagnosis in brachial plexus injury patients undergoing nerve transfer operations: retrospective feasibility study

Abstract: Objective The purpose of this retrospective observational study was to assess the feasibility of electrodiagnostic parameters, perioperatively, and to discover optimal values as prognostic factors for patients with brachial plexus injury undergoing nerve transfer operations. Methods We retrospectively reviewed the records of 11 patients who underwent nerve transfer surgery. The patients underwent perioperative electrodiagnosis (EDX) before and approximately 6 months after surgery. We evaluated the compound mus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 30 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…and underwent nerve transfer operations. 4 Providing this information would bolster this study's data integrity and the authors' conclusions regarding the physiological benefits achieved by the techniques employed.…”
Section: Nicholas Zanghimentioning
confidence: 91%
See 1 more Smart Citation
“…and underwent nerve transfer operations. 4 Providing this information would bolster this study's data integrity and the authors' conclusions regarding the physiological benefits achieved by the techniques employed.…”
Section: Nicholas Zanghimentioning
confidence: 91%
“…A study by Son et al found that the compound muscle action potential (CMAP) improved and correlated with the MRC grade as the patients recovered from a brachial plexus injury and underwent nerve transfer operations. 4 Providing this information would bolster this study’s data integrity and the authors’ conclusions regarding the physiological benefits achieved by the techniques employed.…”
mentioning
confidence: 89%